The Green Economic Movement for Sustainable Development and The Role of Green Governance: A Study in Villages in Bali - I Made Sara; Made Sudarma; Komang Adi Kurniawan Saputra (International Journal of Social Science and Business, 2023)
Community The focus of the research problem is whether green governance has a significant role in its linkage to the green economy and sustainable development. Therefore, this study aims to examine the impact of green economy on Village SDGs, and empirically prove the role of green governance as a mediator in the relationship between green economy and the achievement of Village SDGs. The research method used is a quantitative approach through a type of survey research. The subjects of the study involved 636 village heads throughout Bali Province. Data analysis was carried out using factor analysis methods. The results showed that the green economy has a significant positive effect on the achievement of Village SDGs. Furthermore, the mediating role of green governance on the impact of the green economy is empirically proven. The main contribution of this research is to develop village government policies that focus on green behavior and environmental concern to realize the success of Village SDGs. The implications of this study emphasize the importance of village government awareness of the concept of green economy, which needs to be integrated with the vision and mission of village government.